2014
DOI: 10.1177/0004865814530731
|View full text |Cite
|
Sign up to set email alerts
|

Older prisoners: Challenges for inmates and prison management

Abstract: There is considerable evidence pointing towards the growth of older prisoner populations in Australia. This article presents findings from the first large-scale study of older prisoners in Australia (N = 173), examining functional independence, aspects of the prison environment which present difficulties for less able older prisoners, the uptake of prison programs and social functioning from the perspective of older prisoners. Results indicate that 22% of prisoners aged 50 years and older required assistance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…There is qualitative evidence that fear of such victimization limits the level of social engagement of older prisoners, generating experiences of isolation (Dawes, 2009;Wahidin, 2004). Older prisoners have indicated their use of various strategies to manage safety, including avoiding proximity to younger prisoners, and keeping in the vicinity of prison staff and other older inmates (Trotter & Baidawi, 2015). Researchers have concluded that "Older and more frail inmates may devote a substantial portion of their day-to-day existence trying to minimize the dangers of imprisonment" (Aday & Krabill, 2012, p. 213).…”
Section: Social Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is qualitative evidence that fear of such victimization limits the level of social engagement of older prisoners, generating experiences of isolation (Dawes, 2009;Wahidin, 2004). Older prisoners have indicated their use of various strategies to manage safety, including avoiding proximity to younger prisoners, and keeping in the vicinity of prison staff and other older inmates (Trotter & Baidawi, 2015). Researchers have concluded that "Older and more frail inmates may devote a substantial portion of their day-to-day existence trying to minimize the dangers of imprisonment" (Aday & Krabill, 2012, p. 213).…”
Section: Social Factorsmentioning
confidence: 99%
“…As is the accepted norm in this area, a modified definition of 'older prisoner' was adopted for Indigenous prisoners only (45 years and older) to account for the shorter life expectancy in this population (See e.g. Trotter & Baidawi, 2015;Leach & Neto, 2011).…”
Section: Sampling and Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations